The latest innovations in the legal regulation of the labor of convicts convicted of restriction and deprivation of liberty in Ukraine - Iakovets, Iryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article is devoted to the issue of realization of the right to paid work by persons sentenced to restriction of liberty and imprisonment while serving their sentence. These issues have been and remain quite controversial, since, on the one hand, certain categories of convicts are obliged to work while serving their sentence, but others are not. Also, despite the fact that work is in some cases an obligation of convicts, it is one of the means of correction and re-socialization, which determines its positive nature and impact. For many convicts, the time spent in prison may be the first opportunity in their lives to acquire professional skills and engage in regular work. The main purpose of involving prisoners in work should be to prepare them for normal life after release, not to earn money for the penitentiary institution or to ensure that enterprises operate in the interests of other government departments. At the same time, prisoners should not spend their days in monotonous idleness. This is important both for their own well-being and for maintaining law and order in the colony, as unemployed persons are more likely to suffer from depression and behavioral disorders. However, the analysis of recent legislative initiatives shows a change in approaches to the involvement of convicts in labor, and not all of the proposed innovations are positive. The article analyzes these legislative proposals and offers justifications for their inappropriateness.